ANALYSIS OF BENEVOLENCE FUND ACCOUNTING AND MANAGEMENT AT BANK SYARIAH INDONESIA KCP DURI HANGTUAH 1 BENGKALIS - Asnidar Daulay, Rani; Azlina, Nur (Program Studi Manajemen Keuangan Syariah, 2025)
This study aims to analyze the management mechanism of benevolence funds and identify implementation constraints and solutions at Bank Syariah Indonesia (BSI) Sub-Branch Office (KCP) Duri Hangtuah 1, Bengkalis. Benevolence funds are social funds—sourced from late fees, donations, and non-refundable payments—that are excluded from bank operational income. Using a descriptive qualitative method with data gathered through interviews, observation, and documentation, the study evaluates the bank's compliance with Sharia standards.The results demonstrate that the bank's recording, recognition, and reporting of benevolence funds comply with PSAK 109 regarding Accounting for Zakat, Infaq, and Alms. The process involves four stages: collection, segregated recording, social distribution (e.g., poverty relief and education), and supervision by the Sharia Supervisory Board. Key constraints identified include low public literacy, a shortage of local distribution partners, and suboptimal public reporting. To address these, the bank has implemented customer education, local partnerships, and improved internal transparency. The study concludes that while management aligns with Sharia principles, improvements in socialization and reporting transparency are necessary